GENERAL PSYCHOLOGY AND HEALTH - Fernández Castro, Jordi (Anales de Psicología / Annals of Psychology)
The aim of this work is to analyze the relationship between General Psychology and Health. Firstly, we analyze the current concept of Health, emphasizing that Health risks factors are closely related to daily behaviors. Secondly, the knowledge about this relationship between Psychology and health provided from scientific research in learning and emotion is described. From these points on, the conclussions obtained is that fundamentals of scientific knowledge in the field of Psychology are essential to achieve Health improvement.